STUDENTS’ PERCEPTION TOWARD ENGLISH TEACHER PERSONAL QUALITIES AT SEKOLAH MENENGAH UMUM NEGERI IN BENGKULU MUNICIPALITY - Sri Handayani (Linguists : Journal Of Linguistics and Language Teaching, 2015)
The purpose of this study was to investigate the students’ perception toward English teacher personal qualities at SMUN in Bengkulu Municipality. The population involved all of the SMUN students in Bengkulu municipality, which totally was 5384 students. The sample was 10% of the population that was 539 students, which selected by using stratified random sampling technique. The instrument of this study was a questionnaire, which contains English teacher qualities included in five parts, they were teacher appearance, teaching preparation, teacher’s competence, classroom management and evaluation. This research concluded that the most important qualities viewed by SMUN students in the case of teacher appearance were friendly teacher; who do not make the students feel afraid, and teachers with high discipline. While, in the case of teaching preparation, they expected the teachers should  master the teaching materials well, and who suggest their students to study the materials that will be discussed before English classes take place. Furthermore, in the case of teachers’ competence, they hoped the teachers explain the teaching materials clearly, able to speak English very well, and inspire the students’ motivation. In the case of classroom management, they wanted the teachers who are able to make their course interesting, show the same interests in all their students, and  require them to speak English (to the best of their ability) during English classes. At last, in the case of evaluation, they expected the teachers explain their evaluation procedure in the first meeting, and always administer planned tests  not sudden tests